Thermomechanical stress analysis of PV module production processes by Raman spectroscopy and FEM simulation. (September 2017) - Beinert, Andreas J.; Romer, Pascal; Büchler, Andreas; Haueisen, Viola; Aktaa, Jarir; Eitner, Ulrich
Abstract: Raman spectroscopy is used for measuring stress in microelectronic devices [1] as well as in solar cells [2, 3]. However, on PV module level it has not been examined yet. We transfer the method in order to enable the experimental determination of thermomechanical stress in PV modules. For this purpose the stress in non-soldered, soldered and laminated solar cells is measured by a confocal Raman spectrometer. Additionally we simulate the thermomechanical stress induced by soldering and lamination by finite element modelling. Considering the initial stress state of the solar cells and a linear elastic material model of EVA, the results show a good agreement. By Raman spectroscopy we find the compressive stress in the solar cell after lamination to add up to 53 ± 6 MPa.